2016
DOI: 10.1093/jnci/djw231
|View full text |Cite
|
Sign up to set email alerts
|

Role of CPS1 in Cell Growth, Metabolism, and Prognosis in LKB1-Inactivated Lung Adenocarcinoma

Abstract: Background: Liver kinase B1 (LKB1) is a tumor suppressor in lung adenocarcinoma (LADC). We investigated the proteomic profiles of 45 LADC cell lines with and without LKB1 inactivation. Carbamoyl phosphate synthetase 1 (CPS1), the first ratelimiting mitochondrial enzyme in the urea cycle, was distinctively overexpressed in LKB1-inactivated LADC cell lines. We therefore assessed the role of CPS1 and its clinical relevance in LKB1-inactivated LADC. Methods: Mass spectrometric profiling of proteome and metabolome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 54 publications
5
67
1
Order By: Relevance
“…It has been shown that in human lung adenocarcinoma (LADC), CPS1 mRNA expression was highest in tumors with LKB1 loss (24). Similarly, LADC with LKB1 loss exhibited higher CPS1 protein expression by analyzing a tissue microarray (23). Furthermore, high expression of CPS1 was found to be associated with worse overall survival.…”
Section: Association Of Cps1 Expression With Lung Adenocarcinoma Patimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in human lung adenocarcinoma (LADC), CPS1 mRNA expression was highest in tumors with LKB1 loss (24). Similarly, LADC with LKB1 loss exhibited higher CPS1 protein expression by analyzing a tissue microarray (23). Furthermore, high expression of CPS1 was found to be associated with worse overall survival.…”
Section: Association Of Cps1 Expression With Lung Adenocarcinoma Patimentioning
confidence: 99%
“…Carbamoyl phosphate plays a crucial role in arginine metabolism and pyrimidine biosynthesis, serving as a precursor for both processes (22). CPS1 has been shown to play a role in metabolism and cell growth of LKB1-inactivated lung adenocarcinomas and CPS1 expression in lung adenocarcinoma tumors has been associated with worse overall survival (23). Mechanistically, CPS1 has been shown to sustain pyrimidine levels and DNA synthesis in KRAS/LKB1 lung cancer cells (24).…”
Section: Introductionmentioning
confidence: 99%
“…LKB1-mutant cells showed a decrease in AMPK phosphorylation even upon treatment with a known AMPK activator AICAR which is an intermediate of the purine biosynthesis pathway acted upon by ATIC, the rate-limiting enzyme of this pathway (126). Inducing overexpression of CPS1 in LKB1-inactivated lung adenocarcinoma cell lines or CPS1-negative lung adenocarcinoma cell lines did not induce cell growth (121). This suggested that the role played by CPS1in cell growth might be complemented by other genes in CPS1-negative cell lines.…”
Section: Novel Interactions Of Atic May Underlie Malignant Transformamentioning
confidence: 97%
“…CPS1 is a mitochondrial enzyme that catalyzes the first committed step of the urea cycle and is critical in preventing accumulation of toxic ammonia. When CPS1 is knocked down in LKB1-inactivated lung adenocarcinoma cells, there was a reduction in the level of metabolites associated with purine synthesis, and in cell growth (121). LKB1is a master kinase found to be mutated in 20% of non-small cell lung cancers and in mesothelioma cell lines.…”
Section: Novel Interactions Of Atic May Underlie Malignant Transformamentioning
confidence: 99%
See 1 more Smart Citation